2001
DOI: 10.1007/bf02296191
|View full text |Cite
|
Sign up to set email alerts
|

On measurement properties of continuation ratio models

Abstract: acceleration model, adjacent category models, continuation ratio models, cumulative probability models, hierarchical relationships between IRT models, invariant item ordering, monotone likelihood ratio, polytomous IRT models, sequential model, stochastic ordering,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 39 publications
0
55
0
Order By: Relevance
“…Fortunately, there are several theoretical results that bridge the gap between these two scales. Several researchers have established results concerning the conditional distributions of ζ givenỸ , andỸ given ζ , for a variety of binary (Grayson 1988;Huynh 1994) and polytomous (Hemker et al 1996(Hemker et al , 1997(Hemker et al , 2001; Van der Ark 2005; Van der Ark and Bergsma 2010) item response models (see Hemker 2000, andVan der Ark, 2001, for reviews). Of particular interest here is the property of stochastic ordering of the latent trait by the sum score, meaning that ifỹ 1 <ỹ 2 then P ζ > z|Ỹ =ỹ 1 ≤ P ζ > z|Ỹ =ỹ 2 for any z. Stochastic ordering is implied by the property that a model has a monotone likelihood ratio (MLR), meaning that ifỹ 1 <ỹ 2 then…”
Section: Sum Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, there are several theoretical results that bridge the gap between these two scales. Several researchers have established results concerning the conditional distributions of ζ givenỸ , andỸ given ζ , for a variety of binary (Grayson 1988;Huynh 1994) and polytomous (Hemker et al 1996(Hemker et al , 1997(Hemker et al , 2001; Van der Ark 2005; Van der Ark and Bergsma 2010) item response models (see Hemker 2000, andVan der Ark, 2001, for reviews). Of particular interest here is the property of stochastic ordering of the latent trait by the sum score, meaning that ifỹ 1 <ỹ 2 then P ζ > z|Ỹ =ỹ 1 ≤ P ζ > z|Ỹ =ỹ 2 for any z. Stochastic ordering is implied by the property that a model has a monotone likelihood ratio (MLR), meaning that ifỹ 1 <ỹ 2 then…”
Section: Sum Scoresmentioning
confidence: 99%
“…Since the sum score is observed but ζ is not, SOL is the useful property for making inferences concerning latent traits using sum scores. All binary item response models with monotonic item response functions exhibit MLR and thus SOL (Grayson 1988;Huynh 1994), but of the polytomous models only the partial credit (Masters 1982) and rating scale (Andersen 1977;Andrich 1978a, b) models have the properties of MLR or SOL (Hemker et al 1996(Hemker et al , 1997(Hemker et al , 2001. Van der Ark (2005), however, showed that polytomous models that do not guarantee SOL may still exhibit it in practice.…”
Section: Sum Scoresmentioning
confidence: 99%
“…Polytomous IRT models are commonly divided into the cumulative probability models, continuation ratio models, and adjacent category models (Agresti, 1990;Hemker, Van der Ark, & Sijtsma, 2001;Mellenbergh, 1995;Molenaar, 1983). Each class assumes unidimensionality; that is, the k items in the test share one unidimensional latent variable, and local independence; that is, for a k-dimensional vector of item scores X = x,…”
Section: Three Classes Of Polytomous Irt Modelsmentioning
confidence: 99%
“…. , m, and M i0 (θ ) = 1 for x < 1, and M ix (θ ) = 0 for x > m. Examples of CRMs are the sequential Rasch model (Tutz, 1990), and the nonparametric sequential model (Hemker et al, 2001). These models assume monotonicity for M ix (θ ) (Equation (7)).…”
Section: Three Classes Of Polytomous Irt Modelsmentioning
confidence: 99%
See 1 more Smart Citation